Evaluation of the MIKE SHE Model in a Cold Region - Oogathoo, Shalini; Prasher, Shiv O; Rudra, Ramesh P; Patel, Ramanbhai M (Journal of Agricultural Engineering, 2011)
Given its rapid urbanization, the Canagagigue Creek watershed, located in Grand River Basin (Ontario, Canada), is subjected to shifting hydrological patterns. Consequently, surface runoff was simulated using a watershed-scale model MIKE SHE. The model was calibrated with four years of data and validated with another four years data. Satisfactory levels of overall correlation (RÂ²) between monitored and model-simulated monthly runoff were: 0.87 and 0.77 for the calibration and validation periods, respectively. Corresponding values of the Nash-Sutcliffe coefficient, 0.86 and 0.75, were similar. The model was also used to simulate different management scenarios, urbanization, deforestation, conversion of pastureland into agriculture, diversification of corn system into cash crops, and application of tile drainage. Urbanization showed little impact on surface runoff as increase in urbanized area was a small fraction of the watershed area. Deforestation considerably increased (11%) the total flow. Change in cropping patterns and installation of drainage system had marginal impacts on the surface runoffs. Overall, the model was able to simulate surface runoff reasonably well on monthly and annual basis, although slightly poorer on daily basis. It was concluded that the model could be used to investigate hydrological behaviour of the watersheds in cold climate.